Relationships between psychopathological symptoms, pandemic-related stress, perceived social support, and COVID-19 infection history: a network analysis in Chinese college students - Lee, Chi Kei Krystal; Chan, Kwun Nam Joe; Wong, Sau Man Corine; Wong, Hou Sem Gabbie; Lei, Hiu Ching Janet; So, Yuen Kiu; Fung, Shi Cheng Vivian; Chu, Sai Ting Ryan; Chung, Kar Kin Albert; Cheng, Pak Wing Calvin; Lo, Ka Ying Heidi; Chan, Wai Chi; et al. (Frontiers in Psychiatry, 2024)
Introduction: Previous COVID-19 research has applied network analysis to examine relationships between psychopathological symptoms, but rarely extended to potential risk and protective factors or the influence of COVID-19 infection history. This study examined complex inter-relationships between psychopathological symptoms, COVID-19 related stressors, perceived social support, and COVID-19 infection history among Chinese university/college students during the peak of fifth pandemic wave using a network analysis approach. Methods: A LASSO-regularised partial correlation network using Gaussian graphical model was constructed in 1395 Chinese university/college students in Hong Kong who completed a survey between 15 March–3 April, 2022. Depressive, anxiety and acute/traumatic stress symptoms were measured by Patient Health Questionnaire-9, Generalized Anxiety Disorder-7 and Impact of Event Scale-6, respectively. COVID-19 related stressors and perceived social support were measured. Network differences by COVID-19 infection history (COVID-network vs. no_COVID-network) and network communities were examined. Results: Our results showed that the most influential nodes were depressed mood, uncontrollable worries and uncontrollable thoughts about COVID-19. The main bridging symptoms were concentration problems and psychomotor problems. The COVID-network, comprising participants with a history of COVID-19 infection only, was significantly stronger than the no_COVID-network. Perceived social support, stress from conflicts with family/friends formed a unique community with negative cognition and suicidal idea in the COVID-network only. Conclusion: Our findings indicate that specific interventions targeting interpersonal conflicts and concentration problems as well as facilitating stress buffering effects of social support may represent effective strategies to reduce psychological distress in university/college students during COVID-19, and should be considered for future pandemic preparedness.